Analisis Kekerasan Pada Pipa Yang Dibengkokan Akibat Pemanasan - Sidi, Pranowo; Wahyudi, M. Thoriq (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2012)
Pipe bending process needs special attention because it makes different mechanical properties. Increasing hardness cause materials brittle. The purpose of this study was to analyze the distribution of force on the part of the pipe as a result of the heating curves and 8000C 6700c with bending angle 900 and 1800. SA 335 is a pipe specimen with the size of outside diameter 44.5 mm and a thickness of 8 mm. At first, the two pipes is heated to the temperature 6700c and 2 other pipes that are heated to 8000C temperature, then 2 pipes bended at each heating temperature 900 and 1800. After that cut pipes to grab third in replication in each condition 4 pipe. From the test results found that the bending angle effect on hardness values. The greater the bending angle, the higher the hardness value.Keywords: bending, hardness, pipe, heating.